Targeted Delivery of Neutralizing Anti-C5 Antibody to Renal Endothelium Prevents Complement-Dependent Tissue Damage - Durigutto, Paolo; Sblattero, Daniele; Biffi, Stefania; De Maso, Luca; Garrovo, Chiara; Baj, Gabriele; Colombo, Federico; Fischetti, Fabio; Di Naro, Antonio F.; Tedesco, Francesco; Macor, Paolo (Frontiers in Immunology, 2017)
Complement activation is largely implicated in the pathogenesis of several clinical conditions and its therapeutic neutralization has proven effective in preventing tissue and organ damage. A problem that still needs to be solved in the therapeutic control of complement-mediated diseases is how to avoid side effects associated with chronic neutralization of the complement system, in particular the increased risk of infections. We addressed this issue developing a strategy based on the preferential delivery of a C5 complement inhibitor to the organ involved in the pathologic process. To this end, we generated Ergidina, a neutralizing recombinant anti-C5 human antibody coupled with a cyclic-RGD peptide, with a distinctive homing property for ischemic renal endothelial cells and effective in controlling tissue damage in a rat model of renal ischemia/reperfusion injury. As a result of its preferential localization on renal endothelium, the molecule induced complete inhibition of complement activation at tissue level, and local protection from complement-mediated tissue damage without affecting circulating C5. The ex vivo binding of Ergidina to explanted kidney exposed to cold ischemia supports its therapeutic use to prevent post-transplant ischemia/reperfusion injury leading to delay of graft function. Moreover, the finding that the ex vivo binding of Ergidina was not restricted to kidney, but was also seen on ischemic heart, suggests that this RGD-targeted anti-C5 antibody may represent a useful tool to treat explanted organs prior to transplantation. Based on these data, we propose Ergidina as a novel targeted drug to prevent complement activation on the endothelium of ischemic kidney.